Ca2+, fertilization and egg activation - Swann, Karl (Henry Stewart Talks, 2012)
The role of Ca2+ in activating development in eggs of all species, Sperm egg fusion as the event that precedes the Ca2+ signal, Evidence for a sperm factor that triggers Ca2+ release, Discovery of PLCzeta as sperm factor in mammals, Mechanism of Ca2+ oscillations triggered by PLCzeta
Updated at 2020/09/18